EXPLORING HIGH SCHOOL STUDENTS' PERCEPTIONS OF DOLA AI AS A TOOL TO ENHANCE READING COMPREHENSION - Auliani Sudrajat, Ghina Inasya; Hasim, Wahid; Dewi, Sinta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore high school students’ perceptions of the use of Dola AI as a tool to improve reading comprehension in the context of English as a Foreign Language (EFL).Reading comprehension is an important skill, yet it remains a challenge for many students, particularly due to their limited use of effective reading strategies such as skimming and scanning. The integration of artificial intelligence (AI) into education offers new opportunities to support learning through adaptive and interactive technology. This study employed a qualitative descriptive design involving six high school students who had experience using Dola AI in their English language learning activities. Data were collected through semi-structured interviews and analyzed using thematic analysis based on the Braun and Clarke framework. The results indicate that students generally view Dola AI as a useful and user-friendly tool for helping them understand English texts. Key features such as automatic summarization and contextual Question and answer help students identify main ideas and specific information more efficiently. In addition, the use of Dola AI can also reduce cognitive load and increase student engagement in reading activities. However, some students also expressed concerns regarding reliance on AI and the accuracy of the answers it generates. Overall, this study highlights both the potential and the limitations of using AI in reading instruction.